Coronectomy versus total odontectomy of impacted lower third molars with close relation tothe inferior alveolar canal: An open clinical trial. - Hundren Muhammad; Rozh Mumtaz; Dilman Najmaddin; Omed Ikram (Erbil Dental Journal, 2023)
Background and Objective: Coronectomy is the surgical removal of the crown part of a deeply impacted tooth to preserve the inferior alveolar nerve. This study aims to evaluate the consequences of coronectomy compared to complete surgical removal in patients with a high risk of inferior alveolar nerve injury.